2016
DOI: 10.3389/fpsyg.2015.01959
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Emotion Regulation in Spanish Adolescents: Validation of the Emotion Regulation Questionnaire

Abstract: Emotion regulation (ER) is a basic psychological process that has been broadly linked to psychosocial adjustment. Due to its relationship with psychosocial adjustment, a significant number of instruments have been developed to assess emotion regulation in a reliable and valid manner. Among these, the Emotion Regulation Questionnaire (ERQ; Gross and John, 2003) is one of the most widely used, having shown good psychometric properties with adult samples from different cultures. Studies of validation in children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
42
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 46 publications
11
42
0
4
Order By: Relevance
“…In adolescents, boys had higher scores in self-awareness and motivation. These results are in line with other studies on social and emotional competencies which showed that boys use more emotional suppression then girls (Gómez-Ortiz, Romera, Ortega-Ruiz, Cabello, & Fernández-Berrocal, 2016). Previous studies also found that adult women scored higher than men in emotional intelligence but this difference almost disappeared when age was controlled (Fernández-Berrocal, Cabello, Castillo, & Extremera, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…In adolescents, boys had higher scores in self-awareness and motivation. These results are in line with other studies on social and emotional competencies which showed that boys use more emotional suppression then girls (Gómez-Ortiz, Romera, Ortega-Ruiz, Cabello, & Fernández-Berrocal, 2016). Previous studies also found that adult women scored higher than men in emotional intelligence but this difference almost disappeared when age was controlled (Fernández-Berrocal, Cabello, Castillo, & Extremera, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…The lack of variation in ERQ structure across age and type of cancer adds important evidence for the robustness of this measure and its likely utility in studying psychosocial adaptation to cancer. The CR and ES factors in this study were found to be moderately correlated as they have in a number of other studies, eg, previous studies, since Gross and John first provided evidence of the independence of these factors. The moderate overlap among factors suggests that in the context of meeting the challenges of cancer (and in many other contexts), individuals who tend to reappraise stressful situations in attempt to diminish their negative affect also tend to suppress the expression of negative emotions.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the independence of the 2 factors proposed by Gross and John has not been uniformly supported. While some studies have found that an independent, 2‐factor model provided the best fit, eg, the works of Balzarotti et al and Cabello et al, other studies found evidence supporting a correlated factor model, eg, the works of previous studies …”
Section: Introductionmentioning
confidence: 98%
“…Some authors explain this relationship in terms of the attributions of the victims, who tend to blame themselves for their personal characteristics (what is known as characterological self-blame), causing them great emotional distress (Janoff-Bulman, 1979). This indicates that self-blame could be a mediating mechanism of the relationship between peer victimization and psychological maladjustment (Juvonen and Graham, 2014), thus making it of interest to develop more complex models that include social cognition variables and emotion regulation that mediate this relationship (Gómez-Ortiz et al, 2016). …”
Section: Discussionmentioning
confidence: 99%